Synthesis of bow-tie carbosilane dendrimers and their HIV antiviral capacity: A comparison of the dendritic topology on the biological process. (October 2019) - Gutierrez-Ulloa, Carlos E.; Sepúlveda-Crespo, Daniel; García-Broncano, Pilar; Malý, Marek; Muñoz-Fernández, Mª Angeles; de la Mata, Fco Javier; Gómez, Rafael
Graphical abstract: Highlights: Versatile synthetic approach designed for anionic bow-tie carbosilane dendrimers. Comparative biomedical study attending to the topology of carbosilane dendrimers. Dendron or bow-tie interact with the biological receptors more efficiently. Topology plays an important role for tuning biological or biomedical applications. Abstract: A simple and versatile synthetic approach was designed for the formation of sulfonate-terminated bow-tie carbosilane dendrimers with different cores as hydroquinone moiety, triazol ring or carbamate group. These systems were designed to compare biological and biomedical properties attending to the shape or topology of the carbosilane dendritic systems: spherical, dendrons and bow-tie architectures. Biocompatibility and HIV antiviral activity were measured in TZM.bl cells as human epithelial cell line. Sulfonate groups at the periphery of the dendritic systems were selected due to the ability of previously reported anionic dendrimers to interact with important receptor in viral infection. Finally, experimental results were compared with theoretical data showing a clear relationship between topology and biological activity, being a parameter to consider for exploring biomedical applications.